Caracterização de acessos do banco ativo de germoplasma de mangueira da Embrapa Semiárido - Coelho Junior, Wllamo Pacheco (2024)
Mango is a fruit of great socioeconomic importance, with good representation in the food sector. Therefore, it is necessary to develop research that guarantees the cultivation and diversity of the crop, taking into account aspects such as variety of cultivars, genetic characteristics and cultivation region. In the context presented, a study was carried out in the Active Germplasm Bank of Mango belonging to Embrapa Semiárido, with the objective of characterizing the accessions and quantifying the genetic variability among them, in order to identify the most promising accessions for genetic improvement. The study was carried out from February to October 2023, using 34 accessions for morphological characterization and 10 for fruit evaluation. The results showed significant variations in specific characteristics, such as fruit mass, pulp yield, ventral diameter and transverse diameter. The morphoagronomic characterization revealed high variation for the qualitative and quantitative descriptors. Most accessions presented plants with an open structure and leaves with elliptical limb, acute base and acuminate apex. Regarding the inflorescence, the conical shape and pink color were predominant. The analyses demonstrated variability among the accessions evaluated. The results also indicated reliability in the specifications for different characteristics through the selected accuracy. The most prominent accessions include Pêssego, Pingo de Ouro, Heidi and Ubá. The results obtained demonstrate the existence of genetic variability among the trained accessions, which provides a solid basis for future research related to the management of mango genetic resources. The study also highlighted the genetic stability of the fruits throughout successive evaluation cycles, providing important information for genetic improvement programs.